The Respect of Recommendations Provided in an International Travelers' Medical Service: Far From the Cup to the Lips. Issue 2 (27th November 2012) - Muller, Jean Michel; Simonet, Anne Laure; Binois, Raphaelle; Muggeo, Elisabeth; Bugnon, Pierre; Liet, Jérome; Duong, Michel; Chavanet, Pascal; Piroth, Lionel
Abstract : Background: It is not clearly known how frequently the recommendations given to travelers are followed, and what factors could encourage compliance with these recommended measures. Methods: Adults consulting at a Medical Department for International Travelers (International Travelers' Medical Services, ITMS) in October and November 2010 were asked to answer a questionnaire before their journey. They were also contacted for a post‐travel telephone interview to determine whether they had followed the recommendations regarding vaccinations and malaria prevention, and the reasons for poor or noncompliance with these recommendations. Results: A total of 353 travelers were included, with post‐travel data available for 321 of them. Complete compliance with all the recommendations (vaccinations and malaria chemoprophylaxis) was observed in 186/321 (57.9%) of the travelers. Only 55.6% (233/419) of the prescribed vaccinations were given, with huge variability according to the type of vaccine. Only 57.3% (184/321) of the patients used a mosquito net. Among the 287 prescriptions for antimalarial drugs, 219 (76.3%) were taken correctly, 37 (12.9%) were taken incorrectly (noncompliance with the duration and/or dosage), and 31 (10.8%) were not taken at all. Traveling to areas of mass tourism (Kenya/Senegal), consulting their general practitioner (GP), and being retired were significantly and independently associated with better overall compliance in univariate and multivariate analyses. Conclusions: Compliance could be improved by focusing on factors associated with poor compliance to improve the advice given to less compliant travelers, by providing clear information tailored to each traveler, with a focus on key messages, and by improving coordination between ITMS and GPs.